Kids get cooking the egg: a kid's video guide to food & cooking. ([s.l.] : Goldhil Entertainment, 2005)
Puppets Herb and Bea enjoy watching Kids Get Cooking from their diner. They love art, science, cooking, comedy and songs in the show and so will you. Learn recipes, experiments, crafts and more. Kids get cooking is a kids' video at its most delicious!